Extending the Structural View of Class B GPCRs. Issue 12 (December 2017) - de Graaf, Chris; Song, Gaojie; Cao, Can; Zhao, Qiang; Wang, Ming-Wei; Wu, Beili; Stevens, Raymond C.
Abstract : The secretin-like class B family of G protein-coupled receptors (GPCRs) are key players in hormonal homeostasis. Recent structures of various receptors in complex with a variety of orthosteric and allosteric ligands provide fundamental new insights into the function and mechanism of class B GPCRs, including: (i) ligand-induced changes in the relative orientation of the extracellular and transmembrane receptor domains; (ii) intramolecular interaction networks that stabilize conformational changes to accommodate intracellular G protein binding; and (iii) allosteric modulation of receptor activation. This review provides a comprehensive analysis of the structural, biochemical, and pharmacological data on class B GPCRs for understanding ligand–receptor interaction and modulation mechanisms and assessing the potential implications for drug discovery for the secretin-like GPCR family. Trends: Methodological developments in X-ray crystallography and cryo-electron microscopy have enabled the determination of the first full-length and G protein-coupled structures of class B G protein-coupled receptors (GPCRs). Structural comparison of different class B GPCR–ligand complexes provides insights into the molecular mechanisms of receptor activation, including: (i) ligand-induced conformational changes of extracellular and transmembrane domains; (ii) intramolecular interaction networks facilitating G protein coupling; and (iii) negative and positive allosteric modulation of receptor activation. The new structures of class B GPCRs reveal novel allosteric binding sites. The structural details of the binding modes of negative and positive allosteric modulators provide new templates for structure-based drug discovery for this pharmaceutically relevant receptor family.